Tuberculosis bacilli detection in Ziehl-Neelsen-stained tissue using affine moment invariants and extreme learning machine - Muhammad Khusairi, Osman; Mohd Yusof, Mashor, Prof. Dr.; Hasnan, Jaafar, Assoc. Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/